Hepatic artery injury during left hepatic trisectionectomy for colorectal liver metastasis treated by portal vein arterialization. (2015) - Hokuto, Daisuke; Nomi, Takeo; Yamato, Ichiro; Yasuda, Satoshi; Obara, Shinsaku; Yamada, Takatsugu; Kanehiro, Hiromichi; Nakajima, Yoshiyuki
Highlights: This is a case report of hepatic artery injury during left hepatic trisectionectomy for colorectal liver metastasis treated by portal vein arterialization (PVA). Fatal liver failure after hepatectomy was avoided by PVA. Subsequential portal hypertension was successfully treated by coil embolization of the PVA. PVA seems to be the only way to rescue a patient when hepatic artery reconstruction is impossible, it is important for hepatopancreatobiliary surgeons to know this procedure. Abstract: Portal vein arterialization (PVA) has been applied as a salvage procedure in hepatopancreatobiliary surgeries, including transplantation and liver resection, with revascularization for malignancies. Here we describe the use PVA as a salvage procedure following accidental injury of the hepatic artery to the remnant liver occurred during left hepatic trisectionectomy for colorectal liver metastases (CRLM). A 60-year-old man with cancer of the sigmoid colon and initially unresectable CRLM received 11 cycles of hepatic arterial infusion chemotherapy with 5-fluorouracil (1500 mg/week), after which CRLM was downstaged to resectable. One month after laparoscopic sigmoidectomy, a left trisectionectomy and wedge resection of segment 6 were performed. The posterior branch of the right hepatic artery, the only feeding artery to the remnant liver, was injured and totally dissected. Because microsurgical reconstruction of the artery was impossible, PVA was used; PVA is the sole known procedure available when hepatic artery reconstruction is impossible. The patient then suffered portal hypertension, and closure of arterio-portal anastomosis using an interventional technique with angiography was eventually performed on postoperative day 73. Therefore, it is considered that because PVA is associated with severe postoperative portal hypertension, closure of the arterio-portal shunt should be performed as soon as possible on diagnosing portal hypertension.